Spatiotemporal impacts of the Anthropocene on small mammal communities, and the role of small biological preserves in maintaining biodiversity - Viteri, Maria C.; Hadly, Elizabeth A. (Frontiers in Ecology and Evolution, 2022)
The multi-faceted impacts of the Anthropocene are increasingly modifying natural ecosystems and threatening biodiversity. Can small protected spaces conserve small mammal diversity across spatial and temporal scales of human impact? We identified small mammal remains from modern raptor pellets and Holocene archaeological sites along a human modification gradient in the San Francisco Bay Area, CA and evaluated alpha and beta diversity across sites and time periods. We found that Shannon diversity, standardized species richness, and evenness decrease across modern sites based on level of human modification, with no corresponding change between Holocene sites. Additionally, the alpha diversity of modern sites with moderate and high levels of human modification was significantly lower than the diversity of modern sites with low levels of human modification as well as all Holocene sites. On the other hand, the small mammal communities from Jasper Ridge Biological Preserve, a small protected area, retain Holocene levels of alpha diversity. Jasper Ridge has also changed less over time in terms of overall community composition (beta diversity) than more modified sites. Despite this, Holocene and Anthropocene communities are distinct regardless of study area. Our results suggest that small mammal communities today are fundamentally different from even a few centuries ago, but that even relatively small protected spaces can partially conserve native faunal communities, highlighting their important role in urban conservation.